INSTRUMENTASI PENGUKURAN PANJANG DAN BERAT BADAN BAYI BERBASIS ATMEGA 16 - , NUR ROHMAN PRAWIRO UTOMO; , Hidayat Nur Isnianto,S.T.,M.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Measurement is the activity of comparing physical quantities of objects and events in the real world ( Wikipedia ) . Field that studies regarding measurement and measuring instruments in Electrical Engineering Diploma Program is Instrumentation and Measurement , which includes about measuring scale , measuring instruments , and the precision . Infant growth should be monitored regularly to determine whether the health of the baby takes place in an optimal or not . The terms / parameters usually to monitor the baby's growth is based on the growth in length and weight of the baby . In general, the type of baby weights used are conventional , which is tied with a cloth hanging scales . Similarly, infant length measurement tool is generally used in the body is still using the meter readings. The meter is still analog often cause errors in the reading of the results of measurements of length and weight of the baby . Based on that designed a Baby Body Length Measurement and Weight - Based Infant ATmega16 , where the tool is used ultrasonic sensors and Flexiforce in reading the measurement results will be easier because the measurement readings are displayed digitally via LCD display 16x2 with accuracy and error rate which is quite low .